Contribution of food groups to sodium and potassium intakes by their ratio in Korean adults - Choi, Mi-Kyeong; Kim, Nam-Young; Lee, Yeon-Kyung; Heo, Young-Ran; Hyun, Taisun; Oh, Se-Young; Park, Hyeryun; Ro, Hee-Kyong; Lyu, Eun-Soon (Progress in Nutrition, 2019)
Background/Aims: Koreans have relatively high sodium intakes, and a higher sodium-to-potassium (Na/K) ratio is associated with increased mortality resulting from cardiovascular diseases. The purpose of this study was to analyze the dietary patterns and food groups that contribute to sodium and potassium intakes according to dietary Na/K ratio in Koreans. Methods: A 24-hour dietary recall was collected twice from 640 healthy adults (aged 19-69 years) in four Korean provinces. The subjects were divided into groups of Na/K